Sociodemographic Determinants of COVID-19 Vaccine Hesitancy, Fear of Infection, and Protection Self-Efficacy - Pearl A. McElfish; Don E. Willis; Sumit K. Shah; Keneshia Bryant-Moore; Martha O. Rojo; James P. Selig (SAGE Publishing, 2021)
Objectives: Arkansas COVID-19 vaccine uptake has been lower than the national average. This study examined associations between sociodemographic factors and COVID-19 vaccine hesitancy, fear of infection, and protection self-efficacy. Methods: Adults either residing, having employment, or receiving health care in Arkansas (n = 754) participated in an online survey between October 30, 2020 and January 16, 2021. Participants were recruited in both rural and urban areas from 6 Arkansas primary care clinics. Survey questions addressed sociodemographic factors, COVID-19 infection fear, protection self-efficacy, and COVID-19 vaccine attitudes. Bivariate and multivariable logistic regression models were used to assess associations between dependent variables and respondents' sociodemographic characteristics, COVID-19 infection fear, and COVID-19 protection self-efficacy. Results: About 38% of participants reported COVID-19 vaccine hesitancy. Age, sex, race, and education were significantly associated with COVID-19 and general vaccine attitudes. Odds of COVID-19 vaccine hesitancy decreased as age increased (OR = 0.98; P  < .01). Women had higher odds of COVID-19 vaccine hesitancy than men (OR = 1.52; P  < .05). Respondents with a high school diploma and below and respondents with some college or a technical degree had greater odds of COVID-19 vaccine hesitancy (OR = 2.58; P  < .001; and OR = 1.97; P  < .01, respectively) compared to respondents with a 4-year college degree. Black/African American respondents had greater odds of COVID-19 vaccine hesitancy compared to White respondents (OR = 3.08; P  < .001). No significant difference was observed among rural and urban respondents regarding COVID-19 vaccine hesitancy; however, respondents in rural areas were more likely to report low general vaccine trust compared to those in urban areas (OR = 1.87; P  < .01). Respondents reporting no fear (OR = 5.51; P  < .001) and very little fear (OR = 1.95; P  < .05) of COVID-19 had greater odds of COVID-19 vaccine hesitancy compared to respondents who feared COVID-19 infection to a great extent. Conclusions: COVID-19 vaccine hesitancy and general trust in vaccines differ significantly among age, sex, race, and education. These trust and hesitancy patterns are challenges for achieving population immunity and follow similar patterns of vulnerability to COVID-19. Vaccination programs and interventions must consider these differences in COVID-19 vaccine hesitancy and general vaccine trust to alleviate COVID-19 disparities. Findings make a significant contribution in evaluating vaccine hesitancy among a large, diverse sample from a rural state.